Effect of menopause on arterial stiffness and central hemodynamics: A pulse wave analysis-based cross-sectional study from Gujarat, India - Jayesh Dalpatbhai Solanki; Devanshi Nishantbhai Bhatt; Ravi Kanubhai Patel; Hemant B Mehta; Chinmay J Shah (Wolters Kluwer Medknow Publications, 2021)
Background: Menopause, a cardiovascular risk in mid-life women, is studied in terms of blood pressure mostly. Arterial stiffness (AS) and central hemodynamics (CH) are direct surrogates measured by pulse wave analysis (PWA) with no study from our region. Objective: We studied AS, CH in relation to menopause using PWA. Materials and Methods: A cross-sectional study was performed in 134 middle-aged females divided into groups with or without menopause. Oscillometric PWA done by Mobil-o-Graph (IEM, Germany) gave - AS like augmentation pressure, augmentation index at heart rate (HR) 75, aortic pulse wave velocity (aPWV), and total AS pulse pressure amplification; CH like aortic blood pressure, cardiac output and related parameters, peripheral resistance, stroke work, prevalent brachial/central hypertension, and raised central pulse pressure. They were further compared between groups, in relation to body mass index (BMI) and by multiple regressions with P < 0.05 as statistical significance. Results: Postmenopausal women were significantly elder, physically inactive with comparable BMI and showed higher AS (only aPWV was significantly different) and CH. BMI was unrelated to AS or CH in postmenopausal group. Age (except for aPWV), BMI, and HR (except for AIx@75) were insignificant predictors, while systolic blood pressure (SBP) in premenopausal and diastolic blood pressure (DBP) in postmenopausal group was major AS predictors. Age, HR, and BMI were insignificant predictors, while SBP more than DBP was significant predictors of CH. Conclusions: In obese, predominantly sedentary midlife Gujarati women, menopause negatively affects AS and hemodynamics, central more than peripheral. Menopause accelerates cardiovascular aging, independent of BMI, and age that calls for further studies.